THE INFLUENCE OF MUMIJO EXTRACT ON BLOOD COAGULATION PARAMETERS IN DOGS (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This study investigates the effects of Mumijo extract at a dose of 1 mg/kg on certain blood coagulation parameters in dogs. The experiment was conducted on five dogs, and various parameters were measured at baseline, 30 minutes, and 60 minutes after the administration of the extract. These parameters included blood clotting time, plasma recalcification time, plasma tolerance to heparin, and other related coagulation factors. The findings suggest subtle changes in coagulation profiles, particularly in blood clotting time, fibrinogen levels, and fibrinolytic activity, indicating the potential influence of Mumijo extract on hemostasis in canines.